David Dickson. Alternative technology and the politics of technical change. Glasgow : Fontana : Collins, 1974. 358 p. - Hodara B., Joseph (Estudios Demográficos y Urbanos, 1975)
DAVIS DICKSON, Alternative Technology and the Politics of Technical Change, Glasgow, Fontana/Collins, 1974.